2013
DOI: 10.3922/j.psns.2013.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pleasant visual stimulation on attention, working memory, and anxiety in college students.

Abstract: Different emotional reactions can be induced by the presentation of visual stimuli with affective content. Emotional stimuli are processed and linked with cognitive functions, such as attention, memory, and anxiety, and have implications in the mental health field. Previous studies have reported that positive and negative emotions tend to change cognitive processes in individuals, ultimately resulting in better and worse performance, respectively. Many studies have emphasized the crucial role of affect in dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…This result is similar to previous research findings that depressive patients had lower language learning and memory test results than those without depression and showed the most consistent lack especially in cognitive tasks involving concentration, work memory and decision-making [28]. Since emotions can reinforce the selection of a behavior negatively or positively and play an important role in memory [25], depression is thought to have influenced visual memory. Thus, more active development and application of an intervention program to improve executive function and memory need to be carried out in the future research on depression and cognitive function.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This result is similar to previous research findings that depressive patients had lower language learning and memory test results than those without depression and showed the most consistent lack especially in cognitive tasks involving concentration, work memory and decision-making [28]. Since emotions can reinforce the selection of a behavior negatively or positively and play an important role in memory [25], depression is thought to have influenced visual memory. Thus, more active development and application of an intervention program to improve executive function and memory need to be carried out in the future research on depression and cognitive function.…”
Section: Discussionsupporting
confidence: 81%
“…This was an unexpected result given that previous studies reported that anxiety weakened thinking or concentration, and as a result, patients with anxiety were easily distracted and had difficulty in concentrating [25], and it is contradictory to the reports of decreases in executive function and anecdotal memory [29]. In addition, it is not consistent with previous studies which reported that individuals' anxiety levels had a significant impact on psychological test results, the influence was more prominent in older people, and thus, excessive anxiety or psychological strain led to lower intelligence test results [4].…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Moreover, positive emotions will also activate the amygdala and when activated, the amygdala will mediate connections with the cortex and facilitate the processes of memory formation such as encoding, recalling, and recognition. 19 On the contrary, if the aversive visual stimulations are exposed, high levels of anxiety are presented and there will be a decline in working memory and attention. 20 Also, less technological advances in a rural areas, such as Internet access or ownership of computers which also provide visual stimulation would make the children in rural areas to not use visuospatial memory as often as children in the urban areas.…”
Section: Discussionmentioning
confidence: 99%